Manajer Pendidik Profetik dalam Konstruksi Kesalehan Makrifat - Mulkhan, Abdul Munir (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
Similar to other graduates of the Faculty of Islamic Education and Teaching, those graduated from the Islamic Education Management study program are also educators,prophetic super-leader based on cognizance intelligence (ma’rifat)- which is an empiricalform of the sense of God presence when the God Spot – an analysis by Zohar andMarshall- works. Prophetic super-leaders are professional managers encouraging learningmotivation and organizing education in more civilized way within national framework.Whereas, the Islamic Education Management learning process is based on the IslamicEducation Management Technique and built upon Islamic Education ManagementScience, that is derived from the Islamic Education Management Philosophy.Meanwhile, this philosophical aspect is rooted on the philosophy of Tarbiya which infact is an applied Islamic philosophy. Therefore, the Faculty of Islamic Education andTeaching urgently needs to arrange Tarbiya philosophy as vision accomplishment of being“Excellent and Outstanding in Integrating and Developing Islamic Education andScience for Civilization” since the Tarbiya philosophy and its derivation are foundationof the mission implementation of “Developing Education Based on Islamic, Sciencetific,Tehcnological, Art, and Indonesian context.” Without such an independent theory, thepractice of Islamic Education will only be a kind of follower instead of leader or superleader. At least, there shuld be an obvious statement that the adopted theory is notagainst the concept of Ma’rifah in Islam.